Concomitant Medication Use With Xiyanping Injection and the Risk of Suspected Allergic Reactions: A Nested Case–Control Study Based on China’s National Medical Insurance Database - Tong, Xunliang; Zhu, Xiaochen; Wang, Chunping; Zhou, Yifan; Yan, Yingying; Zhan, Siyan; Zhu, He; Han, Sheng; Cheng, Yinchu (Frontiers in Pharmacology, 2022)
Introduction: Xiyanping injection (XYP), a type of Traditional Chinese Medicine, is widely used and often applied in combination with other medications in treating bronchitis, tonsillitis, and bacillary dysentery in China. In recent years, an elevated risk of allergic reactions has been observed following XYP, but whether concomitant medication use contributes to this risk is still unknown. Objective: This study aims to investigate the association between the concomitant use of XYP and the 25 most frequently co-applied medications with suspected allergic reactions for China’s patients receiving XYP. Methods: A nested case–control study was conducted using the sampling data from 2015 China’s Urban Employees Basic Medical Insurance and Urban Residents Basic Medical Insurance database. Four anti-allergic marker drugs were used to evaluate suspected allergic reactions. Univariate analyses and multivariable conditional logistic regression were conducted, and results were reported as odds ratios (ORs) with a 95% confidence interval (CI). Sensitivity analyses were performed on the expanded sample by including those prescribed with anti-allergic marker drugs on the same day as XYP and then stopped XYP on the next day. Results: Out of 57,612 participants with XYP prescription, we obtained 949 matched case–control pairs. Multivariable conditional logistic regression revealed that seven concomitant medications including gentamicin [OR = 4.29; 95% CI (2.52, 7.30)], cefoperazone-sulbactam [OR = 4.26; 95% CI (1.40, 13.01)], lidocaine [OR = 2.76; 95% CI (1.79, 4.25)], aminophylline [OR = 1.73; 95% CI (1.05, 2.85)], ribavirin [OR = 1.54; 95% CI (1.13, 2.10)], potassium chloride [OR = 1.45; 95% CI (1.10, 1.91)], and vitamin C [OR = 1.32; 95% CI (1.03, 1.70)] were associated with increased risk, while cefathiamidine [OR = 0.29; 95% CI (0.16, 0.51)] was associated with reduced risk. Sensitivity analysis on 2,438 matched pairs revealed similar findings. Conclusion: Increased risks for suspected allergic reactions were found for the concomitant use of XYP with seven medications. Our data suggest that gentamicin, cefoperazone-sulbactam, lidocaine, and ribavirin should be applied with precautions for patients receiving XYP, and further studies on drug interactions and allergy mechanisms are warranted.